Hematology profile of Sumatran Orangutan (Pongo abelii) in the Sumatran Orangutan Quarantine Center, Sibolangit, Indonesia - Maiyus Musrianti; Triva Murtina Lubis; Ahmad Damhoeri (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
This research aims to obtain hematological database of healthy Sumatran orangutans (Pongo abelii) at the Sumatran Orangutan Quarantine Centre, in Batu Mbelin, Sibolangit, North Sumatra, Indonesia. This secondary datacomes from hematological examination results in 52 healthy Sumatran orangutans in Batu Mbelin, from May 2003 to August 2010. This research used a factorial complete randomized design (CRD) that has two factors namely, gender as the first factor and age as the second factor. Data was analyzed using analysis of variance (ANOVA). The results of ANOVA show that gender affects (P0.05) on the value of mean cell hemoglobin concentration (MCHC) in Sumatran orangutans. Age influences (P0.05) on the lymphocytes and monocytes Sumatran orangutans. The results of least significant different (LSD) test of the lymphocyte show that there are significant differences (P0.05) between the lymphocyte value of infants and that of juveniles. The lymphocyte value of infant is also significantly different (P0.05) that of adolescent. While the lymphocyte value of adolescent and juveniles are not significant different. The results of LSD test of the value of monocytes show that there is a very significant difference (P0.01) between the monocyte value of infants and that of juveniles. Furthermore, the value of infant’s and adolescent’s monocytes issignificantly different (P0.05). However, the value of adolescent’s and juvenile’s monocytes does not show any influences. Interaction of sex influences on the red blood cell (RBC) of Sumatran orangutans whereas age do notinfluences on the RBC. The results of Duncan test show that there are significant differences (P0.05) between the RBC values of adolescent female orangutans and adolescent male orangutans. Other hematological values do not show any effects on both gender and age